Correlation of Reduced Interlayer Charge Transfer with Antiphase Boundary Formation in BixSn1–xSe–NbSe2 Heterostructures. Issue 5 (8th February 2017) - Mitchson, Gavin; Bauers, Sage R.; Schädlich, Philip; Ditto, Jeffrey J.; Johnson, David C.
Abstract : Heterostructures of alloyed Bi x Sn1– x Se layers, 0 ≤ x ≤ 1.0, interleaved with NbSe2 monolayers, were prepared by using the modulated elemental reactants technique to investigate the occurrence of antiphase boundaries as a function of Bi concentration. A Rietveld refinement of the c ‐axis structure of the x = 0.50 compound revealed a reduced gap distance between the Bi plane in the Bi x Sn1– x Se layers and the Se plane in the NbSe2 layers and an increased internal Se–Se plane spacing within the Bi x Sn1– x Se layers relative to the end member compounds, suggesting increased interaction between the layers at this composition. High‐angle annular dark‐field scanning transmission electron microscopy (HAADF STEM) images showed no antiphase boundary formation in the Bi x Sn1– x Se layers for x = 0.24, some antiphase boundary formation when x = 0.50, and increased antiphase boundary formation for x = 0.73. Correlated with the absence of antiphase boundary formation for values of x < 0.50 and the increasing presence of antiphase boundaries for x ≥ 0.5, electrical transport measurements showed interlayer charge transfer initially increased with x, then decreased as x was increased to 0.50 and beyond. Abstract : Understanding interlayer interactions in 2D heterostructures will be critical to advance the field. This work explores a correlation between the composition and atomic structure of the Bi x Sn1– x Se layers with the electrical transport properties of the (Bi x Sn1– x Se)1+ δ NbSe2 heterostructure and discusses the results in the context of recent work to understand the interaction.